Identifying fecal microbiota signatures of colorectal cancer in a Vietnamese cohort - Nhung, Pham Thi Tuyet; Le, Hang Thi Thu; Nguyen, Quang Huy; Huyen, Dao Thi; Quyen, Dong Van; Song, Le Huu; Van Thuan, Tran; Tran, Tam Thi Thanh (Frontiers in Microbiology, 2024)
BackgroundColorectal cancer (CRC) is among the top three causes of global cancer mortality. In Vietnam, CRC is the third leading cause of death in women and the fourth cause of cancer mortality in men. A large number of metagenomic studies have reported the relationship between altered composition and function of the gut microbiota with CRC, but this relationship in low- and middle-income countries including Vietnam (with an estimated population of 100.3 million people in 2023, ranking 16th largest country by population in the world) is not well-explored.MethodsWe collected clinical data and fecal samples from 43 CRC patients and 44 healthy control subjects. The total community DNA of microorganisms was extracted from the fecal samples and analyzed for microbiota composition using Illumina MiSeq amplicon sequencing targeting the V3–V4 region of the 16S rRNA gene.ResultsWe identified a significant difference in the overall fecal microbiota composition between CRC patients and healthy controls, and we detected several CRC-associated microbial signatures in fecal samples of Vietnamese patients with CRC, which overlapped with signatures from other countries and meta-analyses. Although patients with (n = 8) and without (n = 35) type 2 diabetes (T2D) exhibited distinct gut microbiota composition compared to healthy controls, increased relative abundances of putatively pathogenic species including Parvimonas micra, Peptostreptococcus stomatis, and Prevotella intermedia were consistent biomarkers for CRC. In contrast, several health-associated species were significantly depleted in CRC patients such as Lactobacillus johnsonii and Bifidobacterium longum in CRC/non-T2D patients, Ruminococcus species, Bacteroides uniformis, and Phascolarctobacterium faecium in CRC/T2D patients, and Butyricicoccus pullicaecorum in both CRC groups combined.ConclusionOur findings confirm alterations in gut microbiota composition in CRC in a pilot Vietnamese cohort and highlight several gut microbial taxa that may have inhibitory or driver roles in CRC. This and future studies will enable the development of cancer diagnostics and treatment strategies for CRC in Vietnam, with a focus on targeting the microbiota.